STUDI NUMERIK RANCANGAN ALAT PENYEDOT MERKURI PADA MESIN PEMBUAT BOHLAM DITINJAU BERDASARKAN HEAT TRANSFER - Joko Jumiyanto; Sutrisno Sutrisno; Prajitno Prajitno (Politeknik Negeri Jakarta, 2019)
The purpose of this study is to observe the pattern of fluid flow on a bulb making machine. The design problem of a mercury suction device is some of the mercury and the exhaust heat from the chimney is sucked in imperfectly towards the outlet. These imperfections occur due to the chimney design and power at the outlet fan. Variations in speed at the bulb-making machine outlet are the most effective looking simulation. CFD simulation is done using fluent ansys. The results of the simulation show the heat transfer phenomenon that occurred. At a speed of 6 m/s the maximum heat air produced is 30.5C. The speed variation in the most effective bulb making machine in this study is 15 m/s. because the surrounding air is almost close to initial temperature which is equal to 27.7C. Keep in mind that by increasing the speed value it will reduce the level of efficiency of the tool.